Comparative Study of Clinical Profile and Outcome Among Variceal and Nonvariceal Bleeding in a Tertiary Referral Hospital of Nepal During Covid Pandemic (Nepalese Medical Journal, 2022)
Introduction: Upper Gastrointestinal Bleeding is a common medical emergency that is broadly classified into variceal and non-variceal bleeding. Preendoscopicemperical treatment is based on clinical findings and laboratory parameters. The article aimed to compare these parameters among variceal and non-variceal bleeding.Materials and Methods: This is a retrospective descriptive study conducted in a tertiary level referral hospital after taking approval from the Institutional review board. The data included was from September 2020 to August 2021. All patients with relevant data who underwent upper GI endoscopy were enrolled. The clinical and laboratory parameters were compared using appropriate statistical tests.Results: A total of 85 patients were studied with 40 (47.06%) in the variceal and 45 (52/94%) in the non-variceal group. Significantly more patients in the variceal bleeding group had a history of alcohol consumption (85% vs 60%) and smoking history (52.50 % vs 31.10%) compared to the non-variceal group. Jaundice, ascites, splenomegaly, low platelet count, and high INR all were predictors of variceal bleeding (p